A Model Transformation for Automated Concrete Syntax Definitions of Metamodeled Visual Languages - Mezei, Gergely; Lengyel, László; Levendovszky, Tihamér; Charaf, Hassan (Electronic Communications of the EASST, 2006)
Metamodeling techniques are popular in describing the rules of special domains, but these techniques do not support defining presentation for these domains , namely the concrete syntax. The aim of our research is to provide a method to create the concrete syntax for metamodeling systems in a flexible, efficient way. Several domain-specific languages have been created that support defining the concrete syntax, i.e. the visualization. The main concern of this paper is to present a model transformation method that processes our presentation definitions and transforms them automatically into source code. The source code implements a plug-in capable of editing the models. A termination analysis for the presented method is also provided.